Determining correct tracheal tube insertion depth by measuring distance between endotracheal tube cuff and vocal cords by ultrasound in Chinese adults: a prospective case-control study - Xuanling Chen; Wenwen Zhai; Zhuoying Yu; Jiao Geng; Min Li (BMJ Open)
Objectives Unrecognised malposition of the endotracheal tube can lead to severe complications in patients under general anaesthesia. The purpose of this study was to verify the feasibility of using ultrasound to measure the distance between the upper edge of saline-inflated cuff and the vocal cords.Design Prospective case-control study.Setting A tertiary hospital in Beijing, China.Methods In this prospective study, 105 adult patients who required general anaesthesia were enrolled. Prior to induction, ultrasound was used to identify the position of the vocal cords. After intubation, the endotracheal tube (ETT) was fixed at a depth of 23 cm at the upper incisors in men and 21 cm in women. The depth of intubation was verified by video-assisted laryngoscopy. The distance between the upper edge of the saline-inflated cuff and the vocal cords was measured by ultrasound; the ideal distance was considered to be 1.9–4.1 cm.Results Among the 105 cases, two cuffs were too close to the vocal cords and one too far away from the vocal cords. These diagnoses were made by ultrasound and were in agreement with results from direct laryngoscopy. The overall accuracy of ultrasound in identifying malposition of the cuff was 100.0% (95% CI: 96.6% to 100%). The sensitivity, specificity, positive predictive value and negative predictive value of ultrasound were, respectively, 100% (95% CI: 96.5% to 100%), 100% (95% CI: 29.2% to 100%), 100% (95% CI: 96.5% to 100%) and 100% (95% CI: 29.2% to 100%).Conclusion Identification of the upper edge of the saline-inflated cuff and the vocal cords by ultrasound to assess the location of the ETT is a reliable method. It can be used to avoid malposition of the ETT cuff and reduce the incidence of vocal cords injury after intubation.Trial registration number ChiCTR-DDD-17011048.